نمط تطوير المنهج الدراسي لقسم تعليم اللغة العربية على أساس تكنولوجيا المعلومات نظريا وتطبيقيا - Ahmad Arifin; Mukhlis Anshari (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
This study seeks to compare and describe the pattern of curriculum development for Arabic language learning in tertiary education on a theoretical and practical level, and the subject of this research study is the pattern of curriculum development for the Arabic Education Department at UIN Antasari and IAIN Palangka Raya. The results of this study indicate that the pattern of curriculum development in these two programs has considered all existing and required components in the national BAN-PT accreditation and these two programs have also achieved an “A” accreditation. On a practical level, the curriculum implementation model developed by the two Arabic education curriculum includes a curriculum containing local knowledge and learning technologies. In the use of learning technology to improve the language skills of Arabic Education Department students at UIN Antasari using the TOAFL, test developed and managed by Language Development Unit at UIN Antasari, while the Arabic Education Department at IAIN Palangka Raya uses online Arabic from the Electronic University of Saudi Arabia as an Arabic language test for foreigners.